50 communications activities, icebreakers, and exercises - Garber, Peter R. (50 Activities Series., 2008)
Have fun presenting these activities and build your employees? communication skills in just minutes. Communication plays such a big part in our lives today. Yet sometimes we get busy and forget just how important communication is to our success, relationships and happiness. 50 Communication Activities, Icebreakers and Activities is a great way to: Increase participants? awareness of how they communicate; Help them to build expertise in a variety of essential skills and competencies; Prepare them to deal effectively with the many types of communication challenges they face every day. Each activ.